TASAWWUF DALAM KAJIAN MODERN - Abdul Wahab Syakhrani; Nikmatul Chusnia, Zulfatul Karimah (CV. Adiba Aisha Amira, 2023)
Sufism is a way to heal the human heart from worldly desires in order to know and get closer to Allah SWT. Sufism is an important thing for humans who want to reach the level of ma'rifatullah. The history of the development of Sufism goes through five periods: 1) the formation period 2) the development period 3) the consolidation period 4) the philosophical period 5) the purification period. The steps towards a life of tasawwuf are tazkiyatun nafsi, mujahadah and riyadloh through several stages, namely: Repentance, Wara', Zuhud, Kefaqiran, Patience, Tawakkal, ridlo.